2001
DOI: 10.1007/s005950170170
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscope-Assisted Versus Conventional Restorative Proctocolectomy with Rectal Mucosectomy

Abstract: To assess the advantages of a laparoscope-assisted proctocolectomy with ileal J-pouch anal anastomosis compared with conventional procedures, we retrospectively analyzed the results of the two procedures as follows: Eleven patients including five patients with familial adenomatous polyposis (FAP) and six with ulcerative colitis (UC) underwent a laparoscope-assisted proctocolectomy and hand-sewn ileal J-pouch anal anastomosis at our department from June 1997 to November 1999. This laparoscope-assisted colectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 14 publications
1
45
0
2
Order By: Relevance
“…However, with advances in technology and experience of laparoscopic surgery, more favourable results have been stated. Several studies have reported the feasibility and safety of laparoscopic assisted total colectomy for ulcerative colitis in the elective setting, and shown the advantages of laparoscopic assisted total colectomy such as reduced postoperative pain, earlier return of intestinal function, decreased length of hospital stay, and improved cosmesis (Marcello et al, 2000;Hashimoto et al, 2001;Seshadri et al, 2001;Gill et al, 2004;Kienle et al, 2005;Larson et al, 2005). On the basis of these results, several studies have evaluated the feasibility and safety of minimally invasive surgery for selected patients with severe ulcerative colitis (Dunker et al, 2000;Bell & Seymour, 2002;Marceau et al, 2007;Fowkes et al, 2008;Watanabe et al, 2009;Holubar et al, 2009;Chung et al, 2009;Maggiori et al, 2010;Telem et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…However, with advances in technology and experience of laparoscopic surgery, more favourable results have been stated. Several studies have reported the feasibility and safety of laparoscopic assisted total colectomy for ulcerative colitis in the elective setting, and shown the advantages of laparoscopic assisted total colectomy such as reduced postoperative pain, earlier return of intestinal function, decreased length of hospital stay, and improved cosmesis (Marcello et al, 2000;Hashimoto et al, 2001;Seshadri et al, 2001;Gill et al, 2004;Kienle et al, 2005;Larson et al, 2005). On the basis of these results, several studies have evaluated the feasibility and safety of minimally invasive surgery for selected patients with severe ulcerative colitis (Dunker et al, 2000;Bell & Seymour, 2002;Marceau et al, 2007;Fowkes et al, 2008;Watanabe et al, 2009;Holubar et al, 2009;Chung et al, 2009;Maggiori et al, 2010;Telem et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Gerade beim Morbus Crohn ist in vielen Fällen mit intraabdominellen Abszessen zu rechnen. Bekannte Abszesse von entsprechender Größe und Erreichbarkeit können CToder ultraschallgesteuert drainiert werden und stellen a priori kein Ausschlusskriterium für die laparoskopische Chirurgie dar [16,17] [5,20,21,23]. Aufgrund bisheriger Erfahrungen kann derzeit der Einsatz laparoskopischer Resektionsverfahren in der Therapie der Colitis ulcerosa nicht als Standard empfohlen werden und wird nur in Zentren durchgeführt.…”
Section: Konventionell Laparoskopischunclassified
“…Insbesondere die erhöhte perioperative Morbidität durch Immunsuppression, Mangelernährung und durch Entzündung hervorgerufene Vulnerabilität des Gewebes lassen minimalinvasive Techniken kritisch erscheinen. Nichtsdestotrotz berichten mehrere Autoren über die sinnvolle Anwendung der Laparoskopie bei Patienten mit CED [1, [3][4][5][6]. …”
unclassified
“…Patients with benign diseases such as ulcerative colitis (UC) and familial adenomatous polyposis (FAP) may be ideal candidates for laparoscopic (procto) colectomy. This procedure remains controversial because of significantly extended operating time compared to that of open procedures [4,6,[9][10][11][12][13], although the difference has come to be minimal with increasing experience in laparoscopic technique [11]. In addition, previous reports revealed that pneumoperitoneum with carbon dioxide, which is commonly used to obtain a good operative field in laparoscopic surgery, is associated with severe cardiopulmonary complications, some of which may be lethal [3,5,8].…”
mentioning
confidence: 98%